Water-soluble and air-stable [2Fe-2S]-metallopolymers: A new class of electrocatalysts for H2 production via water splitting. (3rd July 2019) - Glass, Richard S.; Pyun, Jeffrey; Lichtenberger, Dennis L.; Brezinski, William P.; Karayilan, Metin; Clary, Kayla E.; Pavlopoulos, Nicholas G.; Evans, Dennis H.
Abstract: [2Fe–2S] organometallic complexes are effective electrocatalysts for the reduction of weak acids in acetonitrile to generate molecular hydrogen (H2 ) (hydrogen evolution reaction, HER). Incorporation of such a [2Fe–2S] catalytic site into metallopolymers has been achieved using atom transfer radical polymerization (ATRP). These well-defined polymers have been structurally characterized by SEC, 1 H NMR and IR spectroscopy. These metallopolymers catalyze the electrochemical reduction of acetic acid in acetonitrile. In addition, [2Fe–2S] metallopolymers appended with amino groups were shown to be water-soluble and potent electrocatalysts for H2 production at pH 7. In addition to the exceptional activity of these [2Fe–2S] metallopolymers in water, these catalysts maintain catalytic activity in air unlike comparable molecular catalysts. Graphical Abstract: UF0001